A gênese das gêneses instrumentais: o projeto no uso de máquinas colhedoras de cana-de-açúcar no Brasil e na Austrália - Narimoto, Lidiane Regina (2015)
The mechanization of sugarcane harvesting in Brazil has been presenting significant growth since 2007. The machines used in the fields were originally designed in Australia and were transferred to Brazil in the 70 s. Since its original conception, the design has suffered several modifications and improvements. In ergonomics, it is known that the appropriation of artifacts leads to a process of construction and reconstruction of uses and devices, so that the design continues in usage. With this regard, the present study aimed to analyze the process of design in use of sugarcane harvester machines and to contribute to the understanding of how users design. Considering that the machine was originated in Australia, the study also aimed to conduct a comparative study between the two situations, based on the principles of antropotechnology. Furthermore, given the historical participation of users in design process of sugarcane harvesters, the study also aimed to verify whether this participation still exists now that the design is controlled by multi-national equipment manufacturers. For this purpose, three case study were conducted in Brazil and two in Australia, according to the principles of Ergonomic Work Analysis. The obtained results describe the studied situations, the activity and operation, the modifications in machine s design performed by the harvesting teams, the elaboration process and the need for design improvements. The modifications in machines design were divided into three categories: structural, functional and operational. Structural modifications aimed to adapt the technology to Brazilian conditions: the soil characteristics and the duration of the harvesting season in the country. Functional modifications aimed to solve design problems not anticipated by designers during design process. Operational modifications represented the contribution of users and their activity to the design. In Brazil, several modifications were found and they were elaborated through the articulation of competences of two actors: harvester operator and harvester mechanic. Besides the differences in the amount of modifications, other differences between the two countries were the work organization and the harvesting strategies. It can be concluded that: 1) design in use is essential to adapt a technology to local conditions of usage; 2) the genesis of instrumental genesis is in the junction of operators activity and of mechanics inventory to practice bricolage as a way of designing, as well as the existence of social spaces of interaction between these subjects; 3) users participation, which has always been essential to the design of sugarcane harvester machines, is still crucial and can be reached through a dialogical approach of design.